Evaluasi Program KOTAKU (Kota Tanpa Kumuh) di Sawah Lebar Baru Kota Bengkulu - Ulvansyah, Fhandemi; Indarti, Sri; Darmi, Titi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research is to analyze the evaluation of the kotaku program (city without slums) in New Wide Paddy Fields in Bengkulu City. This research is a qualitative descriptive research. Qualitative descriptive research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The primary data is data obtained from field observations by researchers, interviews with the Office of Public Works and Spatial Planning. Secondary data is data that supports the issues to be discussed, which were obtained from executing the kotaku program (city without slums) in Sawah Lebar Baru, Bengkulu City and the people of Sawah Lebar Baru, Bengkulu City. Research data collection techniques are observation, interviews and documentation. Data analysis using data reduction, data presentation, inference and verification. Based on the results of the study, it can be concluded that the evaluation of the implementation of the City Without Slums (KOTAKU) program in Sawah Lebar Village has been going quite well but not optimal. In its implementation, there have been many construction projects that have been carried out that are able to meet what is needed by the Sawah Lebar Village, such as drainage.